Antipsychotic Medication (Safety/Risk) during Pregnancy and Breastfeeding - Einarson, Adrienne (Current Women's Health Reviews, 2010)
It is important to evaluate the safety of antipsychotic drugs in pregnancy and the postpartum, especially as most women with schizophrenia need to continue their treatment during pregnancy and breastfeeding. With the increasing use of second generation antipsychotics, which cause less hyperprolactinemia-induced infertility than was the case with older drugs, the number of women with schizophrenia becoming pregnant will likely increase. In this review, I discuss the current available, evidenced-based information regarding the safety of antipsychotic drugs used in pregnancy. These include the first generation (chlorpromazine, fluphenazine, haloperidol, loxapine, perphenazine, prochlorperazine, promethazine, thioridazine, trifluoperazine) and second generation (aripiprazole, clozapine, olanzapine, quetiapine, risperidone, ziprasidone). To date, there has been no definitive association between use of these agents and an increased risk of birth defects or other adverse outcomes. Women who are pregnant or breastfeeding and require treatment should always discuss the risks/benefits of pharmacotherapy with their own physician. The evidenced-based information contained in this paper will be of use in their joint decision.
Keywords: breastfeeding